Co-delivery of cisplatin and CJM-126 via photothermal conversion nanoparticles for enhanced synergistic antitumor efficacy. (4th December 2017) - You, Chaoqun; Wu, Hongshuai; Wang, Mingxin; Gao, Zhiguo; Zhang, Xiangyang; Sun, Baiwang
Abstract: Polymeric biomaterials that can be smartly disassembled through the cleavage of the covalent bonds in a controllable way upon an environmental stimulus such as pH change, redox, special enzymes, temperature, or ultrasound, as well as light irradiation, but are otherwise stable under normal physiological conditions have attracted great attention in recent decades. The 2-(4-aminophenyl) benzothiazole molecule (CJM-126), as one of the benzothiazole derivatives, has exhibited a synergistic effect with cisplatin (CDDP) and restrains the bioactivities of a series of human breast cancer cell lines. In our study, novel NIR-responsive targeted binary-drug-loaded nanoparticles encapsulating indocyanine green (ICG) dye were prepared as a new co-delivery and combined therapeutic vehicle. The prepared drug-loaded polymeric nanoparticles (TNPs/CDDP-ICG) are stable under normal physiological conditions, while burst drugs release upon NIR laser irradiation in a mild acidic environment. The results further confirmed that the designed co-delivery platform showed higher cytotoxicity than the single free CDDP due to the synergistic treatment of CJM-126 and CDDP in vitro . Taken together, the work might provide a promising approach for effective site-specific antitumor therapy.